Gut-Derived Serotonin Contributes to the Progression of Non-Alcoholic Steatohepatitis via the Liver HTR2A/PPARγ2 Pathway - Wang, Lulu; Fan, Xiangcheng; Han, Jichun; Cai, Minxuan; Wang, Xiaozhong; Wang, Yan; Shang, Jing (Frontiers in Pharmacology, 2020)
The precipitously increasing of Non-alcoholic steatohepatitis (NASH) seriously threatening public health around the world. Presently, the pathogenesis of NASH has not been thoroughly studied yet. We aim to elucidated interplay between serotonin (5-hydroxytryptamine, 5-HT) and NASH. The serum 5-HT levels of Non-alcoholic fatty liver disease (NAFLD) patients and rats were evaluated using LC-QTOF MS/MS. Peripheral Tph1 inhibitor LP533401 and tryptophan (TRP) free diet were administration to NASH rats induced by high fat-sucrose diet. BRL-3A cells was induced by 1mM free fatty acid (FFA) and/or 50 μM 5-HT, then siRNA 5-HT2a receptors (siHtr2a) and PPARγ pharmaceutical agonist was examined. Herein, we found that a markedly correlation between 5-HT and NASH. The absence of 5-HT, through pharmaceutical blockade of Tph1 (LP533401) and diet control (TRP free diet) restraining hepatic lipid load and inflammation factors (TNF-α, IL6, MCP-1) expression. In BRL-3A cells, 50 μM 5-HT induced lipid accumulation and up-regulated the expression of lipogenesis (FAS, CD36, PLIN2) and inflammation response. Specifically, further Htr2a knockdown and PPARγ agonist results revealed that Htr2a promote hepatic steatosis and inflammation by activating PPARγ2. These results suggested that duodenal 5-HT is a risk factor in the pathological progression of NASH. Correspondingly, it may represent an attractive therapeutic target for preventing the development of NASH via regulating Htr2a/PPARγ2 signal pathway.